Langmuir Turbulence in the Auroral Ionosphere: Origins and Effects - Akbari, Hassanali; LaBelle, James W.; Newman, David L. (Frontiers in Astronomy and Space Sciences, 2021)
Theory and observations of Langmuir waves and turbulence induced in the auroral ionosphere by electron beams of magnetospheric-origin are reviewed. The theoretical discussions include a brief description of the electrostatic dispersion relation, excitation of Langmuir waves by electron beams, and the stability of beam distributions. The theory of Langmuir turbulence---including the parametric decay instability and wave collapse---is also briefly discussed. The main focus of the review, however, is on the observations of Langmuir waves and turbulence in the ionosphere by in-situ and ground-based sensors. A summary of five decades of in-situ wave and particle observations is presented and combined with a collection of more recent results from ground-based instruments. The ground-based observations include signatures of Langmuir turbulence in the form of coherent echoes in incoherent scatter radar measurements; signatures of electron beams in the form of auroral morphologies recorded by high-speed, high-resolution optical imagers; and electromagnetic emissions receivers on the ground at high latitudes. Uniting the various observations obtained by the vastly different sensors is shown to provide further insight into the micro-scale processes which occur in the ionosphere. Also discussed in this review is the potential of the ground-based sensors to provide a broader spatial and temporal context for single-point in-situ measurements of such processes.